Factors affecting movements and home ranges in the jay (Garrulus glandarius) - Rolando, Antonio (Journal of Zoology, 1998)
The winter home ranges, movements and density of the jay Garrulus glandarius in the Maremma Natural Park (Tuscany, Italy) are presented, and compared with those already known for the other seasons. The movements of jays were studied for short periods over 6 years by radiotelemetric techniques (26 home ranges), direct observations of movements from vantage points, and transect counts. Summer and autumn ranges were much larger than spring and winter ones. Incremental area plots and auto-overlap analyses showed that, on average, spring ranges increased in area with time without shifting, whereas winter ranges were rather stable. In both periods, however, some birds moved as floaters since the degree of range auto-overlap decreased significantly with time. In winter and spring, range sizes of jays inhabiting different habitats were significantly different, being larger in sites with higher habitat heterogeneity. The structure of home ranges was variable in all seasons; birds showed jointed and disjointed ranges, with one or more activity centres, in all the possible combinations. In every season the average degree of range overlap between jays caught at the same site was rather high and overall actual overlap, when non-tagged birds were also considered, was even higher. No territorial behaviour was ever observed. During summer jays moved into the pinewood for the greater part of the day to collect cicadas, Cicada orni, and returned to the maquis in the evening. During autumn birds regularly moved within the maquis or from the maquis to the pinewood to cache oak (Quercus ilex) acorns. No regular long movements between habitats were observed during spring and winter. Direct observations and analyses of pellets suggested that food was abundant and highly diversified throughout the year. Thus, seasonal movements and home ranges were flexible and mainly controlled by food availability and its distribution in space and time.
Keywords: home range; jay; movements; radiotelemetry; Seasonality